2022
DOI: 10.1002/ptr.7471
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin ameliorates lipopolysaccharide‐induced acute liver injury by inhibiting oxidative stress and inflammation via SIRT1/FOXO1a/SOD2 signaling in rats

Abstract: Acute liver injury (ALI) is a poor prognosis and high mortality complication of sepsis.Paeoniflorin (PF) has remarkable anti-inflammatory effects in different disease models. Here, we explored the protective effect and underlying molecular mechanisms of PF against lipopolysaccharide (LPS)-induced ALI. Sprague-Dawley rats received intraperitoneal (i.p.) injection of PF for 7 days, 1 h after the last administration, and rats were injected i.p. 10 mg/kg LPS. PF improved liver structure and function, reduced hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Excessive ROS formation, disruption of the prooxidant/antioxidant balance and inflammation are critical events in the pathogenesis of liver damage. 29 Altered levels of CORT are known to enhance the toxicity of oxygen radicals by increasing the basal levels of ROS. 30 In the present study, hepatic ROS, and serum and hepatic levels of the stress-related hormone CORT in CUMS mice were concurrently reversed by HT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS formation, disruption of the prooxidant/antioxidant balance and inflammation are critical events in the pathogenesis of liver damage. 29 Altered levels of CORT are known to enhance the toxicity of oxygen radicals by increasing the basal levels of ROS. 30 In the present study, hepatic ROS, and serum and hepatic levels of the stress-related hormone CORT in CUMS mice were concurrently reversed by HT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of these symbiotic beneficial bacteria resulted in lower levels of SCFA, as demonstrated by our results. Several studies had shown that increased LPS in the gut caused intestinal inflammation and disrupted the intestinal barrier, after which LPS entered the circulation, causing oxidative stress and disrupting lipid metabolism in the liver (Li et al., 2022; Zheng & Wang, 2021). In our study, broad bean increased LPS and decreased SCFA levels in the gut, which were consistent with the observation of inflammatory responses and impaired intestinal barriers in the intestinal tract of CGC.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress contributes to inflammation and organ injury during sepsis ( Kumar et al, 2022 ). Various studies have disclosed that inhibition of oxidative stress ameliorates sepsis and/or sepsis-induced multiple organ dysfunctions, including lung, liver, kidney, heart, etc ( Gong et al, 2022 ; He et al, 2022 ; Li X. et al, 2022 ; Li L. et al, 2022 ). The data of our study revealed that MALT1 overexpression increased the levels of serum proinflammatory cytokines, including TNF-α, IL-6, and IL-1β, while MALT1 knockdown decreased these proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%